Effect of varied recovery interventions on markers of psychophysiological stress in professional rugby union - Lindsay, A.; Lewis, J.; Gill, N.; Gieseg, S. P.; Draper, N. (European Journal of Sport Science, 2015)
Rugby union is a physical demanding sport that requires optimum recovery between games to maintain performance levels. Analysis of four unique biochemical markers of stress is measured here to determine which recovery strategy currently in use by a professional team provides the necessary requirements for sustained performance. Urine and saliva samples were collected from 37 professional rugby players before, immediately after and 36 hours after five home games, and analysed by enzyme linked immunosorbent assay and high performance liquid chromatography for urinary myoglobin, total neopterin (NP; NP + 7,8-dihydroneopterin), salivary cortisol and immunoglobulin A. Subjects completed a cold water immersion (CWI) or pool session (PS), donned compression garments, consumed protein and carbohydrate food and fluid, and slept for 8 hours post-game. The following day subjects choose from one or a combination of CWI, PS or active recovery/stretching to complete. There was no difference between the recovery protocols for cortisol, total NP, immunoglobulin A concentration or myoglobin at 36 hours post-game. Immunoglobulin A secretion rate significantly increased above pre-game levels at 36 hours post-game for all protocols; however, protocol three did not increase as much (p = 0.038). Total NP was also significantly increased above pre-game levels at 36 hours post-game for all protocols. This study provides evidence that the immediate post-game recovery intervention following a game of professional rugby union may be the most important aspect of psychophysiological player recovery, irrespective of the "next-day" intervention. The concentrations of total NP and immunoglobulin A suggest these professional rugby players are still in a state of recovery 36 hours post-game.